Treinamento físico e suplementação de flavonóis do cacau: impactos no desempenho físico, memória e respostas neurotróficas, imunoquímicas e de estresse oxidativo em um modelo experimental de envelhecimento por D-galactose - Daniel Massote de Melo Leite (2024)
Aging can promote irreversible effects, causing damage to the body, resulting in a progressive impairment of functional and cognitive abilities. The etiology of aging is still not fully understood, and in order to better comprehend the physiological mechanisms related to aging and improve the quality of life in this population, aging models have been developed in the laboratory using rodents. D-galactose, a reducing sugar, has been used as an animal model that mimics aging. To mitigate the deleterious effects of aging, combined physical training and nutritional interventions have proven effective in controlling metabolic and cognitive deficits in the elderly. Diets rich in flavonols found in cocoa have been used to prevent diseases and attenuate the aging process. Although supplementation with flavonols and combined training can bring various health benefits, the synergistic effects of chronic intake on cognitive and inflammatory parameters associated with aging have not been extensively investigated. To achieve the objectives of this thesis, the work was divided into two studies: 1) Effects of aging on physical performance, memory, inflammatory profile, and oxidative stress in rats; 2) Effects of physical training and/or supplementation with cocoa flavonols on aerobic and muscular strength performance, memory, BDNF, and inflammatory markers in an experimental aging model. In study 1, eight-week-old Wistar rats received 150 mg.kg-1.day-1 of D-Galactose (D-GAL) or saline solution (CON) intraperitoneally for 8 weeks, and their muscle strength and aerobic physical performance were evaluated in the pre, fourth, and eighth weeks of intervention. Short- and long-term memory were assessed in the pre-period and after the eighth week. There was a decrease in aerobic performance in the D-GAL group, including VO2peak (p = 0.044), TTE (p = 0.023) in the 4th week, and work (p = 0.011) in the 4th and 8th weeks of D-GAL (p = 0.041). Long-term memory was reduced in the D-GAL group (p < 0.001) and was associated with increased oxidative stress and decreased IL-10 in the brain and soleus and EDL muscles in the D-GAL group (p < 0.05). The pro-inflammatory ratio of IL-1β / IL-10 in the soleus and frontal cortex was increased in the D-GAL group (p < 0.05). In study 2, two-month-old Wistar rats (n=9 per group) received 150 mg.kg-1.day-1 of D-GAL for 8 weeks and were divided into four experimental groups: (PLA and COCOA) rest, and TC (COCOA and PLA), which performed combined physical training (TC) on alternate days using a ladder (8 sets, 50% to 100% of the maximal load) and treadmill running for 30 min (60% VO2peak), and were supplemented with flavonol-enriched cocoa and/or placebo (45 mg.kg-1.day-1) once daily, 5x per week, for 8 weeks. After the TC, short- and long-term memory were assessed. The TC group achieved greater gains in strength, TTE, VO2peak, and work vs. REST (p < 0.01). In the short-term memory test, the REST.COCOA group restored cognition vs. REST. PLA (p = 0.01). IL-6 cytokine in the hippocampus was reduced in the TC COCOA group vs. TC PLA (p = 0.03). Additionally, TC elevated BDNF in the hippocampus vs. REST. PLA (p = 0.04). Cocoa supplementation was effective in attenuating IL-6 inflammation in the soleus muscle vs. REST.PLA.